The Significant Influence of Exposure to Negative Content on Instagram on the Intolerance Behavior of 11th Grade Students in the Context of Akidah Akhlak Learning - Franty Putri Zubair; Herson Anwar; Firmansah Kobandaha; Muhammad Suriani Shiddiq; Ni'ma M. Alhabsyi (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the significant effect of negative content exposure on Instagram on the intolerance behavior of eleventh-grade students in the context of Akidah Akhlak learning at Madrasah Aliyah Al-Huda, Gorontalo City. The increasing use of Instagram among teenagers, accompanied by the proliferation of content containing hate speech, provocation, discrimination, and intolerant narratives, urges empirical studies on its impact on the formation of students' social behavior. This study employed a quantitative approach with a simple regression design. The study population consisted of all eleventh-grade students at MA Al-Huda Gorontalo City for the 2025/2026 Academic Year, totaling 74 students. Total sampling was used so that all members of the population became research respondents. The research instrument was a questionnaire with a four-point Likert scale consisting of 30 items, which was then tested for validity and reliability before use. The validity test results showed that 25 items were declared valid, while the reliability test obtained a Cronbach's Alpha value of 0.937, categorized as highly reliable. The prerequisite tests included the Kolmogorov-Smirnov normality test yielding significance values of 0.318 and 0.506 (> 0.05), and the linearity test yielding a Linearity significance value of 0.023 (< 0.05). The hypothesis test results using the t-test showed a t-count value of 2.202 > t-table of 1.666 with a significance of 0.031 (< 0.05), so that H₀ was rejected and Hₐ was accepted. The determination coefficient (R²) test results showed a value of 0.063, meaning that negative content exposure on Instagram contributed 6.3% to students' intolerance behavior. It can be concluded that there is a positive and significant effect of negative content exposure on Instagram on the intolerance behavior of eleventh-grade students at MA Al-Huda Gorontalo City in the context of Akidah Akhlak learning.